NILAI-NILAI PENDIDIKAN KARAKTER DALAM NASKAH DRAMA ANAK KERAJAAN BURUNG KARYA SAINI KM DAN NASKAH DRAMA ANAK NENG NONG KARYA M. UDAYA SYAMSUDIN - Zalmasri .; Harris Efendi Thahar; Ngusman . (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: The development of the national living in Indonesia for the last ten years, the character of the people in Indonesia (sources litbang compass 2012) was marked by many events that have a major impact on the degree of weaknesses of the character people in Indonesia. This fact indicates that the relevant literature into instructions to educate character education. The aim of the research; (1) describes the educational values ​​of the characters in a drama chidrentkerajaan burung by Saini KM; (2) describes the educational values of characters in achildren’s drama  Neng Nong by M. Udaya Syamsudin; (3) describe a comparison the educational values ​​of character inchildren’s dramasKerajaan Burung by Saini KMand children’s dramasNeng Nong by M. Udaya Syamsudin. The research was aqualitativeanalysis method and using mimetic capproach. The result of research shows; (a) thevalueofcharacter educationonfaith and devotion;(b) the values​​that emphasizeonhonesty, (c) Thevalueof character education stressed on brilliantine;(d) Thevalueof character education focuseson indicator ssuchaspatient, courage to sacrificeandhard worker;(e) Thevalueof character education straight on caring attitude. Kata kunci: nilai-nilai, pendidikankarakter, drama anak, sastra.